Essential project management functions - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. A functional approach to project management describes a mode of action by which an objective or goal is fulfilled.The project Management Institute (PMI), in its PMBoK guide, 5th edition, identified ten distinct functional modes (knowledge areas) currently used internationally in project management best practice, by which a project objective can be achieved.